O “Efeito Batom” no laboratório: o impacto do priming de recessão econômica no viés atencional feminino para produtos de beleza - Thales Vianna Coutinho (2017)
The “lipstick effect” is characterized by a paradoxical increase in the desire to consume expensive beauty products during periods of economic recession. The initial propositions about the existence of the lipstick effect derive from evolutionary psychology. Recently, an experimental approach to this phenomenon has also been used. Although the initial data support the existence of the lipstick effect, investigations mainly involve psychological questionnaires. The present study aimed to verify if women exposed to economic scarcity bias their attention to beauty products. Thirty-eight women participated in this study (n = 38). They were asked to perform an antisaccade task, which first consisted of reading one of two texts: a passage related to the Brazilian economic crisis (experimental condition) or a neutral passage discussing “the moons of Mars” (control condition). The number and the time of gaze fixation on the images were recorded using eye-tracking. No differences were found between the groups (experimental and control) in terms of the number and time of fixation in the images of beauty products. However, comparing the participants according to the use of contraceptive medication, it was found that those who did not use looked at beauty products more often and for a longer time. This finding may be related to the specificity of the “lipstick effect” in women who do not use this contraceptive method since previous studies have shown that it has a role in mate choice. We argue that the use of contraceptives has reduced female impulsivity, and this is reflected in a lower number of errors during the experiment since the task of antisaccade is considered an inhibitory control measure.